Bio-Inspired Fluorine-Free Self-Cleaning Polymer Coatings - Lionel Wasser (Coatings, 2018)
Bio-inspired fluorine-free and self-cleaning polymer coatings were developed using a combination of self-assembly and UV-printing processes. Nasturtium and lotus leaves were selected as natural template surfaces. A UV-curable acrylate oligomer and three acrylated siloxane comonomers with different molecular weights were used. The spontaneous migration of the comonomers towards the polymer⁻air interface was found to be faster for comonomers with higher molecular weight, and enabled to create hydrophobic surfaces with a water contact angle (WCA) of 105°. The replication fidelity was limited for the nasturtium surface, due to a lack of replication of the sub-micron features. It was accurate for the lotus leaf surface whose hierarchical texture, comprising micropapillae and sub-micron crystalloids, was well reproduced in the acrylate/comonomer material. The WCA of synthetic replica of lotus increased from 144° to 152° with increasing creep time under pressure to 5 min prior to polymerization. In spite of a water sliding angle above 10°, the synthetic lotus surface was self-cleaning with water droplets when contaminated with hydrophobic pepper particles, provided that the droplets had some kinetic energy.